Diseño de un sistema de gestión de calidad, bajo el enfoque de la norma ISO 9001 2008 en la empresa Mármoles Tungurahua - Tasinchana Taco, Cristian Geovanny (2017)
Nowadays due to a economy globalized, where all companies compete in order to get part of the market, the need arises to offer products and services with a high degree of quality that is perceived by the increasingly demanding customers and it must be guaranteed that products contain attractive characteristics valued by them. The presented research project has the objective to design a system of management quality under the focus of the ISO 9001: 2008 norm. The research project was carried out at Mármoles Tungurahua company for the purpose researchers use the inductive method and the expected results with this research were, the design of a quality management system, the lifting of production processes, the identification of the indicators to be reached according to the standard applied and an improvement plan that should be implemented by the company.